E-mediacja jako pozasądowa metoda rozwiązywania sporów konsumenckich - Kotwicka, Wiktoria (Wydawnictwo C.H. Beck, 2017)
The aim of the present study is the analysis of functioning of e-mediations (online mediations) regarding consumer disputes in the Polish legal system in the context of EU regulations (directive regarding ADR in consumer disputes 2013/11/EU and the regulation regarding online system of consumer disputes resolution no. 524/2013). The author describes the concept of e-mediations regarding consumer disputes, their technical aspects, and also the principle of e-mediations proceedings conducted by specialized entities within the framework of the online system of consumer disputes resolutions created in the regulation 524/2013.
Keywords: mediation; e-mediation; Online Dispute Resolution; alternative dispute resolution; consumer disputes; consumer